2017
DOI: 10.1038/nm.4329
|View full text |Cite
|
Sign up to set email alerts
|

Decreased alertness due to sleep loss increases pain sensitivity in mice

Abstract: Extended daytime and nighttime activities are major contributors to the growing sleep deficiency epidemic1,2, as is the high prevalence of sleep disorders like insomnia. The consequences of chronic insufficient sleep for health remain uncertain3. Sleep quality and duration predict presence of pain the next day in healthy subjects4–7, suggesting that sleep disturbances alone may worsen pain, and experimental sleep deprivation in humans supports this claim8,9. We demonstrate that sleep loss, but not sleep fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 67 publications
8
117
0
Order By: Relevance
“…Alertness is known to affect many functions, such as performance, psychological and physiological well‐being, caloric intake, and pain sensitivity . Displaying optimal alertness is thus beneficial, and many studies have attempted to improve alertness using monochromatic or polychromatic light (for review see,).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alertness is known to affect many functions, such as performance, psychological and physiological well‐being, caloric intake, and pain sensitivity . Displaying optimal alertness is thus beneficial, and many studies have attempted to improve alertness using monochromatic or polychromatic light (for review see,).…”
Section: Introductionmentioning
confidence: 99%
“…13 Alertness is known to affect many functions, such as performance, psychological and physiological well-being, caloric intake, and pain sensitivity. [14][15][16][17] Displaying optimal alertness is thus beneficial, and many studies have attempted to improve alertness using monochromatic or polychromatic light (for review see, 18,19 ). Exposure to light improves alertness during nighttime, when melatonin concentrations are usually high and CBT decreases.…”
Section: Introductionmentioning
confidence: 99%
“…While the endocrine system, including proopiomelanocortins and endorphins, is most often linked to pain syndromes, there exists a role for most hormones in acute and chronic pain (Chen, Zhang, & Wang, ; Csaba, ). For instance, a recent study on the role of sleep in naïve noxious pain showed that sleep deprivation exacerbates sensitivity to mechanical and thermal stimuli, an effect that is dependent on prostanoids produced by cyclooxygenases (Alexandre et al, ). There is also a prominent role for hormones in the circadian entrainment of peripheral clocks, particularly glucocorticoids: dexamethasone treatment induces circadian gene expression in cultured rat fibroblasts but not SCN neurons (Balsalobre et al, ).…”
Section: Circadian Control Of Inflammatory Mediatorsmentioning
confidence: 99%
“…A high level of alertness is defined as a state of high sensitivity to incoming stimuli 4 . It is known to affect many psychological and physiological functions, such as performance, caloric intake and pain sensitivity [5][6][7][8] . Polychromatic white light has been shown to significantly improve alertness during the evening and night 3 .…”
Section: Introductionmentioning
confidence: 99%